Analisis Dana ZIS Produktif Terhadap Kesejahteraan Mustahik Melalui Pertumbuhan Usaha Mikro Sebagai Variabel Intervening - Rozikin, Muhammad; Alvionita Ferima, Cynthia; Afsah Novita Sari (Institut Agama Islam Negeri Ponorogo, 2025)
Zakat is an act of worship performed by the Islamic community which has a social value of mutual help. The growth of zakat management institutions increased to help underprivileged people. This research report aims to analyze and test the effect of productive ZIS on mustahik welfare through micro business growth as an intervening variable. The effect of Productive ZIS on micro business growth. The effect of Micro Business Growth on mustahik welfare and the effect of productive ZIS on musthik welfare. The research location is NU Care - Lazis NU Kediri Regency which has a list of superior activities for mustahik economic empowerment. A total of 47 samples of this study were taken as survey data collection. Data analysis was carried out with a quantitative approach using the Path Analysis model of the SmartPLS version 3.0 application. The results of the analysis show that ZIS has a significant positive effect on micro business growth. Micro Business Growth has no effect on mustahik welfare. Productive ZIS has no significant effect on mustahik welfare. The effect of Productive ZIS has no significant effect on mustahik welfare mediated by micro business growth. Assistance in the form of productive ZIS requires supervision and additional resources.